China’s Technological Self-Reliance Strategy in Responding to Western Corporate Monopoly and Dominance in the Technology Sector: A Legal Review of Competition Law across Various Legal Instruments: Strategi Kemandirian Teknologi Tiongkok dalam Menghadapi Monopoli dan Dominasi Korporasi Barat di Bidang Teknologi: Suatu Tinjauan Hukum Persaingan Usaha dalam Berbagai Produk Hukum - Putra, Louis Sebastian Anot; Lie, Gunardi (Indonesian Journal of Law and Economics Review, 2025)
Background (General): Western technological dominance has shaped global markets and innovation trajectories, creating structural imbalances in competition. Background (Specific): China faces this asymmetry with the rise of U.S. legal, economic, and technological pressures, particularly during escalating trade conflicts. Knowledge Gap: While many studies address industrial policy or competition law separately, limited scholarship integrates how China’s legal framework functions simultaneously as market regulation and geopolitical strategy. Aim: This study examines China’s technological self-reliance strategy by evaluating the role of the Anti-Monopoly Law (AML) alongside major industrial policies in countering Western corporate hegemony. Results: Findings demonstrate that China employs AML with dual functionality—disciplining domestic giants such as Alibaba while fortifying national sovereignty against foreign corporate influence—and aligns this with three major initiatives: Made in China 2025, Dual Circulation Strategy, and China Standards 2035 to strengthen manufacturing capability, market independence, and global standard-setting authority. Novelty: Unlike traditional market-driven antitrust systems, China adopts state-oriented “antitrust mercantilism,” integrating competition law with industrial modernization and geopolitical objectives. Implications: The study indicates a shift in global competition norms, where national legal instruments increasingly function not only to balance market fairness but also to challenge structural dominance and redistribute global technological power. Highlights: China integrates antitrust law with industrial policy to strengthen technological independence. The strategy responds directly to Western corporate and geopolitical dominance in global technology. Policies such as MIC 2025, DCS, and China Standards 2035 reinforce sovereignty and global competitiveness. Keywords: Technological Self-Reliance, Anti-Monopoly Law, Industrial Policy, Western Dominance, China Strategy